Methodical principles of anti-doping training in youth sports - Gretsov, A. G.; Vorobiev, S. A. (Theory and Practice of Physical Culture, 2018)
The study was designed to formulate the methodological fundamentals that may be applied to design an anti-doping educational course for junior athletes geared to cultivate zero tolerance to doping, with the educational process driven by their values and motivations. Doping shall be interpreted as a gross violation of the fair play rules of the modern sports by the deliberate and motivated actions resulting in predictable harm, with the relevant problems being discussed within the frame of the general personality values. Doping may be associated with the asocial behavioural models and actions having long-term negative implications. The line of arguments in the educational concept shall be designed with account of the personality ethic and psychology development stages as provided by L. Kohlberg`s theory, with the course being duly customized to the target audience i.e. its age, sporting experience, sport mastery levels and expected professional careers in sports. The educational material shall be delivered on a problem-specific basis application of the relevant socio-psychological education elements. Based on the above provisions, we have designed and implemented a set of 8 anti-doping educational programs supported by the relevant methodological guidelines - including zero tolerance cultivation technology, process design recommendations, graphical teaching aids, and `Tales about sports` for children.